2007
DOI: 10.4135/9781473974104
|View full text |Cite
|
Sign up to set email alerts
|

Air Canada: Selling the Company by the Slice

Abstract: Robert Milton had been fascinated by flying ever since childhood and dreamed of running an airline. But as he grew up and entered the industry, Milton came to see how poorly the major "legacy" airlines performed financially. The romance of flying could not obscure the difficulty of sustaining a profit in this industry. After a series of jobs in the airline industry, Milton came to Air Canada in 1992. While COO of the airline, he became convinced that the various parts of the airline operated separately could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…While the commercial air cleaners tested as part of this study will not be identified, the DIY designs will. D2 and D/S1 were variations of a Corsi–Rosenthal Box (CR Box), a popular, inexpensive design where four or five furnace filters are arranged to form a cube around the inlet side of a box fan. While both configurations were constructed with the same 53 × 61 × 18 cm box fan (Air King, model 9723) and aluminum foil tape (TapePlus), D2 used 51 × 51 × 5 cm PM filters (Tex-Air Filters, MERV 13) while D/S1 used activated carbon filters of the same dimensions (Tex-Air Filters, Odor Relief Carbon).…”
Section: Methodsmentioning
confidence: 99%
“…While the commercial air cleaners tested as part of this study will not be identified, the DIY designs will. D2 and D/S1 were variations of a Corsi–Rosenthal Box (CR Box), a popular, inexpensive design where four or five furnace filters are arranged to form a cube around the inlet side of a box fan. While both configurations were constructed with the same 53 × 61 × 18 cm box fan (Air King, model 9723) and aluminum foil tape (TapePlus), D2 used 51 × 51 × 5 cm PM filters (Tex-Air Filters, MERV 13) while D/S1 used activated carbon filters of the same dimensions (Tex-Air Filters, Odor Relief Carbon).…”
Section: Methodsmentioning
confidence: 99%
“…Creditors, who now controlled 87 percent of Air Canada, were seeking their due after agreeing to accept equity in the newly created holding company as part of the restructuring plan (IAMAW v. Air Canada 2011). Milton's agenda was clear: fragment Air Canada and its regional divisions into a handful of independent, profitable businesses (Jacques and Kepos 2011; Rosenthal, Bova, and Thomas 2007). Shares were issued for Air Canada's lucrative passenger rewards program, Aeroplan, creating previously untapped financial value for prospective shareholders.…”
Section: Economic Restructuring and Industrial Relations At Air Canadamentioning
confidence: 99%